(untitled) (Carte Romanze, 2023)
In the field of linguistic studies on Italian song lyrics, the genre of progressive rock remains one of the most marginal and least appreciated from the point of view of linguistic innovations. Furthermore, the subalternity that is generally recognized in textual composition compared to musical composition (which involves limitations that devalue the literary component of the text) is considered particularly marked in the manifestations of art music, like prog is. Through a linguistic-literary analysis of the texts contained in the first two albums of one of the most representative bands of the genre, Banco del Mutuo Soccorso, the discussion aims to highlight the themes and stylistic features that characterize the language of the authorial couple Francesco Di Giacomo-Vittorio Nocenzi, in order to underline its literariness and originality and define its poetics.